Evaluation of Coconut Based Anacardium occidentale Agroforestry System to Improve the Soil Properties of Coconut Growing Lands in Wet, Intermediate and Dry Zone of Sri Lanka - S. H. S. Senarathne; S. S. Udumann (International Coconut Community, 2019)
This study was intended to assess the impact of coconut based Anacardium occidentale (Cashew) agroforestry systems on soil fertility of degraded coconut lands in wet, intermediate and dry zones of Sri Lanka. Two treatments were evaluated according to randomized complete block design with three replicates. Coconut based agroforestry systems intercropped with A. occidentale and sole coconut were evaluated as two treatments. Soils from three depths were analyzed for its’ chemical, physical and biological properties. According to the esults, higher total N, available P and exchangeable K levels were shown in sole coconut systems than A. occidentale intercropped system while the higher total N levels (2% higher than top soil and 27% higher than deepr soil) were observed in sub soils compared top and deep soils. Higher P content was observed in top soils than in deeper soils. The exchangeable K was observed in higher quantities in sub soil than in deeper soils and was varied with locations. Organic matter content in intercropping of A. occidentale has been increased by 37% and the highest was observed in top soils. Soil bulk density has been reduced by 9% in A. occidentale intercropped system enhancing the root growth. Bulk density has been increased with the depth of the soil. Higher soil microbial activity was observed in A. occidentale intercropped system and it was 22% higher than sole coconut system. Sole coconut system has 50% higher soil moisture percentage and the highest was recorded in sub soils. This study confirms that intercropping of A. occidentale has a positive effect on improving soil fertility of degraded coconut growing soils in wet, intermediate and dry zones of Sri Lanka.